The debate: Is global development adapting to climate change?. (June 2020) - Schipper, E.L.F.; Tanner, T.; Dube, O.P.; Adams, K.M.; Huq, S.
Highlights: A debate considered whether global development was adapting to climate change. The distinction between adaptation or development is often unclear. Adaptation will require transformative development with an equity and justice focus. Abstract: The debate about the relationship between adaptation to climate change and development has been ongoing for over two decades. Adaptation is about risk reduction, the pursuit of opportunity and rethinking investments, planning and behaviour, which is also in many ways what development is about. Yet a distinction between the two is necessary for the existing funding architecture, and to ensure that adaptation is more than just business as usual. We summarise a debate held at the Adaptation Futures 2018 conference to explore whether global development is adapting to climate change, with one side arguing for, the other arguing against. The outcome suggests no obvious winner, in part because there is no clear distinction between what qualifies as exclusively adaptation or development, since some dimensions of each put them in opposition to one another, while other dimensions are mutually reinforcing. Yet, to say that adaptation will take place through development does not sufficiently underscore the need for development to be rethought. Adaptation will require transformative development – that is, development that takes everyone into account and places issues of equity and justice in the centre and adheres to principles of sustainability.